Visualizing the Street: New Practices of Documenting, Navigating and Imagining the City - Dibazar, Pedram; Naeff, Judith (Cities and Cultures, 2018)
From user generated images of street protests in Istanbul and Hong Kong, to professional architectural renderings of future streets, to GPS-tracked walks in London and Amsterdam, and the visualisation of Sydney's urban change via social media, this collection of essays analyses new practices of how we visualise the street. Today, new technologies allow everyone who carries a smartphone to play an increasingly significant role in the production, editing, and circulation of images and such a technological development has constructed new imaginaries of the street and has had a significant impact on the ways in which contemporary streets are understood, documented, navigated, mediated, and visualised. Visualizing the Street investigates the social and cultural significance of these new developments at the intersection of visual culture and urban space. The interdisciplinary essays provide new concepts, theories, and research methods that combine close analyses of street images with the study of the practices of their production, circulation, and ultimate consumption.